STANDARDIZATION AND COMPARATIVE EVALUATION OF AYURVEDIC POLYHERBAL GHRITA FORMULATION WITH MODERN EXTRACTION TECHNIQUE FOR EXTRACTION EFFICIENCY USING REVERSED PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - M, Shelar; L, Sathiyanarayanan; K, Mahadik; S, Gadgil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Sarasvata ghrita (SG) is a polyherbal formulation in Ayurvedic Indian medicinal system, in which ghee is the main ingredient used for extraction. Ghee is 100% lipid, thus its regular use is limited, and there is a lack of quality control profile of SG. Thus, the objective of the study is to develop quality control method for standardization of SG and to analyze manufacturing process of SG and an effective method of extraction to extract phytoconstituents from herbs used in SG to overcome the limitation of SG. Methods: SG was processed as per the traditional method, whereas ethanolic extract (EE) and hydroalcoholic extract (HAE) were obtained by the conventional method and lipid-based extract (LE) was prepared by modern extraction method. SG and all extracts were standardized using newly developed high-performance liquid chromatography (LC) with respect to bebeerine, piperine, 6-shogaol, Î²-asarone, and chebulinic acid. All extracts were analyzed for pesticides, and heavy metal content by LC/mass spectrometry (MS/MS) and inductively coupled plasma/MS, respectively, screened for total polyphenols and flavonoids content, in vitro antioxidant potential, and for assessing its stability over time. Results: The better extraction was observed with maceration extraction using ethanol compared to ayurvedic method and LE method. All extracts were found to have a negligible amount of pesticide and heavy metals and found to be stable for 6 months under accelerated storage condition. Better polyphenols and flavonoid content and in vitro antioxidant potential were resulted in EE. Conclusion: EE showed a better potential in comparison with SG and LE.